A note on the non-planar corrections for the Page curve in the PSSY model via the IOP matrix model correspondence - Norihiro Iizuka; Mitsuhiro Nishida (Journal of High Energy Physics)
Abstract We develop a correspondence between the PSSY model and the IOP matrix model by comparing their Schwinger-Dyson equations, Feynman diagrams, and parameters. Applying this correspondence, we resum specific non-planar diagrams involving crossing in the PSSY model by using a non-planar analysis of a two-point function in the IOP matrix model. We also compare them with Page’s formula on entanglement entropy and discuss the contributions of extra-handle-in-bulk diagrams.